Knowledge-driven economic growth: the case of Sub-Saharan Africa. Issue 1 (2nd January 2020) - Oluwatobi, Stephen; Olurinola, Isaiah; Alege, Philip; Ogundipe, Adeyemi
ABSTRACT: The experience of South Korea, India, China and Singapore reveals that developing economies can fast-track development, leapfrog the stages of development and catch up with advanced economies by putting knowledge capital as the driver of development. If the knowledge economy is therefore an accelerant of development for both advanced and developing economies, it is possible for Sub-Saharan African (SSA) economies to also catch up with advanced economies. It was on this basis that this study assessed the knowledge capacity of SSA and the effect it has on its economic advancement. Given the importance of the interrelatedness among the knowledge economy elements, this study, thus, examined how the interaction effect between the elements of the knowledge economy affects economic growth in 32 SSA countries, for which data were available, over a period of 17 years (1996–2012). Using the System Generalised Method of Moments (SGMM), the study found out that institutions and human capital in SSA mitigate the effect of innovation on economic growth in the region, thus, making it a lean knowledge economy.